Analysis of Reading Interest of High Class Elementary School Students - Putri Sri Wiranda Darus; Dea Mustika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Reading is the key to student learning success in school. The higher students' reading interest not only increases students' knowledge, but also improves student learning outcomes. This study aims to describe the reading interest of high school students in elementary school. This type of research is descriptive qualitative research. The data sources in this study were one homeroom teacher for class V and four students for class V. The data collection techniques in this study used interview, observation, and documentation techniques. The validity of this research data using triangulation techniques, sources and time. Data analysis used the Milles and Huberman model with three stages, namely data reduction, data presentation and conclusion drawing. This research was developed into 5 sub-indicators consisting of frequent reading, reading time, reading varied readings, reading readings that are considered important and looking for reading materials themselves. The results of the study concluded that the reading interest of high-grade students at the State Elementary School 03 Minas has begun to be seen, although it has not been achieved optimally. Because there are still students who have not shown the same interest in reading.